All Days 2011
DOI: 10.2118/148969-ms
|View full text |Cite
|
Sign up to set email alerts
|

Improved Characterization and Performance Assessment of Shale Gas Wells by Integrating Stimulated Reservoir Volume and Production Data

Abstract: Gas flow in shale gas reservoirs occurs primarily from ultra low permeability shale rocks through a complex network of natural and induced hydraulic fractures. Consequently, fracture parameters (conductivity and half length), fracture location and distribution are the dominant factors influencing well drainage volumes and shale gas well performance. Stimulated reservoir volume or SRV, estimated from microseismic event clouds or rate/pressure transient analysis, describes a measurement of overall reservoir volu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 41 publications
(42 reference statements)
0
9
0
Order By: Relevance
“…These methods can reduce computational efforts comparing to the discrete fracture network model, but typically the analytical solution used in these models cannot capture the very long transient behavior in the matrix blocks exhibited by shale gas reservoirs (Cipolla et al, 2010a). In addition, Yin et al (2011) used an enhanced permeability area to approximate the enhancement effect by the network fractures as higher permeable matrix zone in the vicinity of the fractures. In this method, the hydraulic fractures were expressed as the higher permeable grids, and the enhanced permeability area exists along the fracture grid to consider the stimulated reservoir volume.…”
Section: Shale Reservoir Modelingmentioning
confidence: 99%
See 3 more Smart Citations
“…These methods can reduce computational efforts comparing to the discrete fracture network model, but typically the analytical solution used in these models cannot capture the very long transient behavior in the matrix blocks exhibited by shale gas reservoirs (Cipolla et al, 2010a). In addition, Yin et al (2011) used an enhanced permeability area to approximate the enhancement effect by the network fractures as higher permeable matrix zone in the vicinity of the fractures. In this method, the hydraulic fractures were expressed as the higher permeable grids, and the enhanced permeability area exists along the fracture grid to consider the stimulated reservoir volume.…”
Section: Shale Reservoir Modelingmentioning
confidence: 99%
“…For the expression of induced or reactive complex fracture networks around the created hydraulic factures, we took the same approach presented by Yin et al (2011). This is one of the single porosity models with the simple approximation of the enhancement effect by network fractures.…”
Section: Objectives and Approachmentioning
confidence: 99%
See 2 more Smart Citations
“…We generate the "observed" bottom-hole pressure data using the finite difference reservoir simulation coupled with geomechanical modeling for the first 5 years of the production. History matching is performed using the genetic algorithm (Yin et al 2011;Xie et al 2012b) with model parameters and their ranges shown in Table 2. The genetic algorithm is carried out for 20 generations and each generation has a population consisting of 80 realizations.…”
Section: Matrix/fracture Parameter Estimationmentioning
confidence: 99%